Implementation of Healthcare Failure Mode and Effect Analysis (HFMEA) as an Effort to Improve Patient Safety in Hemodialysis Services in Indonesia - Aulia, Ariadne; Dewi, Arlina; Rosa, Elsye Maria (Majalah Kedokteran Bandung, 2025)
Hemodialysis patients are at risk of preventable adverse outcomes as a result of the ongoing medical treatments required throughout their life. Minimizing risk is crucial for ensuring patient safety in healthcare environments. Healthcare Failure Mode and Effect Analysis (HFMEA) is a proactive risk assessment method designed to identify potential failures in healthcare processes and improve the quality and safety of patient care. This qualitative descriptive study aimed to identify potential failure modes in hemodialysis services in Nitipuran Hemodialysis Clinic by implementing HFMEA. A multidisciplinary team was involved as the unit of analysis to identify processes and subprocesses for in-center hemodialysis treatment. The study employed purposive sampling, selecting 10 team members who were directly involved in providing hemodialysis services. Data collected were analyzed using the HFMEA worksheet. Over five weeks, the team convened six times to identify Failure Modes (FMs) and Failure Mode Causes (FMCs), conduct a Hazard Analysis, and determine necessary actions to address the FMCs. Five processes, 23 subprocesses, 74 Failure Modes (FMs), 39 Failure Mode Causes (FMCs) were identified. Based on the Hazard Analysis results, 27 FMCs required corrective actions and thirteen actions were proposed to address the FMCs and improve patient safety based on the findings of this study. Further research is needed to evaluate the effectiveness of the implementation of these corrective actions in improving patient safety.